Respiratory pathogenesis of amoebic gill disease (AGD) in experimentally infected Atlantic salmon Salmo salar - Melanie Leef; Harris, JO; Powell, MD (2005)
The aim of this study was to investigate the respiratory responses of Atlantic salmon, Salmo salar, experimentally affected with amoebic gill disease (AGD). In Series I, arterial blood samples were taken over a 96 h period following amoebae addition to examine potential respiratory effects associated with initial exposure. No major significant treatment effects were found between fish exposed to amoebae and control (non-exposed) fish. Arterial pH (pH a) was seen to be significantly elevated at 48 h in AGD fish relative to the 0 h time point. To investigate the long-term respiratory effects associated with infection, fish were similarly exposed to amoebae and sampled over a 16 d period. As for Series I, caudal blood pH was significantly elevated by Day 2 (48 h) compared to the pre (Day 0)-time point, suggesting that initial exposure to amoebae and/or amoebae attachment may have induced an initial respiratory alkalosis via increased ventilation frequency and/or amplitude. From Day 7 onwards, and coinciding with a significant increase in the percentage of affected gill filaments, blood pH decreased significantly, possibly indicating the onset of the characteristic respiratory acidosis that has previously been described for experimentally AGD-affected Atlantic salmon. Although fish in this study showed up to 90 % AGD-affected filaments, the corresponding respiratory results do not reflect a major acid-base disturbance. Therefore, the findings from the present study support the contention that, although AGD only affects the gill, AGD-associated mortality in Atlantic salmon may not be primarily associated with respiratory failure. Â© Inter-Research 2005.